PENGGUNAAN ENZIM PAPAIN DALAM PAKAN TERHADAP KARAKTERISTIK USUS DAN PENAMPILAN PRODUKSI AYAM PEDAGING - E. Fitasari (BUANA SAINS, 2012)
This research was aimed to evaluate the influence of papain enzyme on fee, intestinal characteristic, microflora and the broiler production performance. There were used 4 treatments : P1 (control), P2 (papain 0.050% w/w), P3 (papain 0.075 w/w), and P4 (papain 0.100%). Observed variables were; intestinal characteristic (pH, intestinal viscosity, intestinal proteolitic enzyme activity, ileum villi height and number) and production performance (consumption, weight gain, feed convertion, carcass weight, and income over feed cost/IOFC). This study was carried out in Randomized Complete Design. The significant influence, tested with Duncan’s Multiple Range test. The result showed that the treatments gave significant difference (p